Unplanned admissions and the organisational management of heart failure: a multicentre ethnographic, qualitative study. Issue 10 (19th October 2015) - Simmonds, Rosemary; Glogowska, Margaret; McLachlan, Sarah; Cramer, Helen; Sanders, Tom; Johnson, Rachel; Kadam, Umesh; Lasserson, Daniel; Purdy, Sarah
Abstract : Objectives: Heart failure is a common cause of unplanned hospital admissions but there is little evidence on why, despite evidence-based interventions, admissions occur. This study aimed to identify critical points on patient pathways where risk of admission is increased and identify barriers to the implementation of evidence-based interventions. Design: Multicentre, longitudinal, patient-led ethnography. Setting: National Health Service settings across primary, community and secondary care in three geographical locations in England, UK. Participants: 31 patients with severe or difficult to manage heart failure followed for up to 11 months; 9 carers; 55 healthcare professionals. Results: Fragmentation of healthcare, inequitable provision of services and poor continuity of care presented barriers to interventions for heart failure. Critical points where a reduction in the risk of current or future admission occurred throughout the pathway. At the beginning some patients did not receive a formal clinical diagnosis, in addition patients lacked information about heart failure, self-care and knowing when to seek help. Some clinicians lacked knowledge about diagnosis and management. Misdiagnoses of symptoms and discontinuity of care resulted in unplanned admissions. Approaching end of life, patients were admitted to hospital when other options including palliative care could have been appropriate. Conclusions: Findings illustrate the complexity involved in caring for people with heart failure. Fragmented healthcare and discontinuity of care added complexity and increased the likelihood of suboptimal management and unplanned admissions. Diagnosis and disclosure is a vital first step for the patient in a journey of acceptance and learning to self-care/monitor. The need for clinician education about heart failure and specialist services was acknowledged. Patient education should be seen as an ongoing 'conversation' with trusted clinicians and end-of-life planning should be broached within this context.